2019
DOI: 10.1007/s42380-019-00030-w
|View full text |Cite
|
Sign up to set email alerts
|

Cost-benefit Analysis of the KiVa Anti-bullying Program in the Netherlands

Abstract: This study performs a cost-benefit analysis of the implementation of the KiVa anti-bullying program in the Netherlands. Specifically, it addressed whether the expected benefits of KiVa for victims in terms of lifetime income are greater than the costs that are made for implementing the program. The KiVa intervention was examined in a randomized controlled trial in the Netherlands in 2012-2014 in 98 Dutch primary schools (target grades US-level 3-4, 8 to 9 years old). A model-based approach was applied to the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Economic arguments are highly influential in progressing policy reform and action in areas such as child protection and childhood development [50,51]. There are few studies evaluating anti-bullying interventions from an economic perspective [21,22]. Recently, Australian researchers evaluated return on investment of implementing the FSFF and found total cost benefits exceed total intervention costs [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Economic arguments are highly influential in progressing policy reform and action in areas such as child protection and childhood development [50,51]. There are few studies evaluating anti-bullying interventions from an economic perspective [21,22]. Recently, Australian researchers evaluated return on investment of implementing the FSFF and found total cost benefits exceed total intervention costs [25].…”
Section: Discussionmentioning
confidence: 99%
“…The authors estimated that preventing high school bullying results in lifetime cost-savings of more than $1.4 million per individual [21]. Another study demonstrated that the KiVa anti-bullying program in the Netherlands generated a return-on-investment (ROI) of €4.04-€6.72, indicating that for every €1 invested €4-€7 would be gained [22]. The cost-effectiveness of the KiVa bullying prevention program was analysed and estimated to be 7879 SEK (€829) for each additional victimfree year gained and 131,321 SEK (€13,823) for each additional QALY gained [23].…”
Section: Introductionmentioning
confidence: 99%
“…Data used in this study stem from the KiVa anti-bullying program in the Netherlands (Huitsing et al, 2020 ; Veenstra et al, 2020 ). The data were collected in May and October 2012, before and at the start of the intervention (Huitsing et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…The model's time horizon was considered sufficient to reflect all important differences between options in 30 studies (61.2%). Only ten models used a 50-year time horizon [50,59] or lifetime horizon [27,28,30,32,56,66,70,72]. In models with a shorter time horizon, only 22 studies (44.9%) justified the use of a shorter time horizon.…”
Section: Model Structurementioning
confidence: 99%
“…Among 46 models that performed parameter uncertainty analysis, 12 studies only addressed univariate sensitivity analysis [26,29,32,39,40,43,56,62,64,66,68,71]. Nine studies only performed probabilistic sensitivity analysis [25,41,44,47,48,54,55,67,72].…”
Section: Datamentioning
confidence: 99%